Observational evidence linking ocean sulfur compounds to atmospheric dimethyl sulfide during Icelandic Sea phytoplankton blooms - LEE, KITACK; Kim, Jun-Seok; Park, Ki-Tae; 박민지; Jang, Eunho; Gudmundsson, Kristinn; Olafsdottir, Solveig R.; Olafsson, Jon; Yoon, Young Jun; Lee, Bang-Yong; 권세윤; Kam, Jonghun (Science of The Total Environment, 2023)
In two Icelandic Sea spring blooms (May 2018 and 2019) in the North Atlantic Ocean (62.9-68.0 degrees N, 9.0-28.0 degrees W), chlorophyll -a and dimethylsulfoniopropionate (DMSP) concentrations and DMSP lyase activity (the DMSP-to-dimethyl sul-fide (DMS) conversion efficiency) were measured at 67 stations, and the hourly atmospheric DMS mixing ratios were con-currently measured only in May 2019 at Storhofdi on Heimaey Island, located south of Iceland (63.4 degrees N, 20.3 degrees W). The ocean parameters for biology (i.e., chlorophyll -a, DMSP, and DMSP lyase activity) were broadly associated in distribution; however, the statistical significance of the association differed among four ocean domains and also between 2018 and 2019. Specifically, the widespread dominance of Phaeocystis, coccolithophores, and dinoflagellates (all rich in DMSP and high in DMSP lyase activity) across the study area is a compelling indication that variations in DMSP-rich phytoplankton were likely a main cause of the variations in statistical significance. For all the ocean domains defined here, we found that the DMS production capacity (calculated using the exposures of air masses to ocean biology prior to their arrivals at Heimaey and the atmospheric DMS mixing ratios of those air masses at Heimaey) was surprisingly consistent with in situ ocean S data (i.e., DMSP and DMSP lyase activity). Our study shows that the proposed computational approach en-abled the detection of changes in DMS production and emission in association with changes in ocean primary producers. 1 1 N scie scopus